Teacher Knowledge Skills in Class to Manage Student Behavior in Facing Challenges and Increasing Learning Success - Wiyono, Hadi; Ramadhan, Iwan; Imanulyaqin, Muhammad Nur; Yas'a, M. Dissha Najiah Al; Zatalini, Adhalia (Journal of Education Reseach and Evaluation, 2025)
The lack of interpersonal skills among teachers remains a barrier to encouraging students to achieve optimal academic achievement. Although these skills are considered important in 21st century learning, their implementation in the field has not shown adequate results. This study aims to analyze the level of teachers' interpersonal skills and evaluate their relationship with student academic achievement. This study used a quantitative approach with a survey design. The subjects were 557 high school students randomly selected as a sample. The data collection technique used a questionnaire developed based on indicators of leadership, teacher attention, understanding, distrust, dissatisfaction, warnings, and assertiveness, with a Likert scale of 1 to 5 as the measurement instrument. Data were analyzed using descriptive and inferential statistics with the help of SPSS software version 29.0. The study results indicate a significant relationship between teacher interpersonal skills and student academic achievement, influencing students' mastery of basic skills. The conclusion of this study confirms that improving teacher interpersonal skills contributes positively to student learning experiences and achievements. These findings indicate the importance of integrating interpersonal skills training into teacher professional development to improve learning effectiveness and the quality of educational outcomes.